Experimental evaluation of arm motion using tri-axial accelerometers based on factorized quaternion approach - Lee, G. X. (2013)
In this paper, we evaluate a factorized quaternion approach for determining the arm orientation experimentally. The proposed approach uses tri-axial accelerometers with consideration of anatomical and sensor constraints. Experiments have been conducted using a wireless sensor network that comprises of tri-axial accelerometer sensor nodes attached to the arm. The results have been benchmarked with a commercial inertial measurement unit to validate the performance and advantages of this new system. Comparable performance in terms of accuracy has been obtained at a much reduced cost and lower power consumption.